Keterkaitan Akuntabilitas dan Transparansi dalam Pencapaian Good Governance - ITB, CUI (Center for Research and Community Services ITB, 2004)
The concept of ‘good governance’ was introduced by some national and international institutions. They defined this concept into some principles. Accountability and transparency are two principles of good governance which need to be prioritized in the implementation of good governance concept. These two principles have close relationship and support each other. Without transparency, there will be no accountability and without accountability, transparency has no meaning. This article is itended to discuss the link and the position of these two principles to achieve good governance